Investigating the Design of Arabic Web Interfaces Using Hofstede’s Cultural Dimensions: A Case Study of Government Web Portals - Khashman, Nouf; Large, Andrew (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study examines the design characteristics of Web interfaces from Arab countries using Hofstede’s cultural dimensions. Organizational and graphical elements on a sample of 15 home pages of government Web portals are examined using content analysis. Element frequency scores were correlated with Hofstede’s dimensions and interpreted based on Marcus and Gould’s (2000) study. The results suggest that Hofstede’s model of culture does not fully reflect the design characteristics of Arabic interfaces. Cette étude examine les caractéristiques d'interfaces web de pays arabes au moyen des dimensions culturelles de Hofstede. Les éléments organisationnels et graphiques d'un échantillon de 15 pages d'accueil de portails gouvernementaux sont étudiés dans le cadre d'une analyse de contenu. Les scores de fréquence des éléments sont mis en corrélation avec les dimensions de Hofstede et interprétés en fonction de l'étude de Marcus et Gould (2000). Les résultats suggèrent que le modèle culturel de Hofstede ne reflète pas pleinement les caractéristiques des interfaces en arabe.